Facing Boldly the Scourge of Praedial Larceny on Food Production in the Caribbean - Wayne G. Ganpat; Wendy-Ann P. Issac (Journal of International Agricultural and Extension Education, 2018)
Agricultural crimes or farm theft,commonly referred to as praedial larceny throughout the Caribbean, impacts significantly on food security through high levelsof economic loss. This paper provides an overview of praedial larceny worldwide, losses in the Caribbean region and some evidence from Trinidad and Tobago where the situation is prevalent. The study was guided by the routine activities theory; identifying the types of criminal acts perpetrated, the level of risks posed to farmers and a special emphasis on the concept of guardianship. Data from group discussions and interviews conducted among farmers in two major areas in Trinidad representing different terrain (flat and hilly areas) and an acknowledged ‘hot spot’ area. The findings show that praedial larceny is no respecter of farmers, farming communities, type of crops, location or farmers’ economic circumstances. Finally, the paper reports on initiatives around the region and suggests other mechanisms which can be introduced to reduce the impact of praedial larceny on food security
Keywords: Praedial larceny; Food security; Routine Activity Theory; Caribbean